A parallel software-defined ultra-low-power receiver for a satellite message forwarding system - Lima, Raffael S. C. G. de; Duarte, José Marcelo L.; Nascimento, Diego V. Cirilo do; Souza Filho, Reinaldo A. de; Xavier-de-Souza, Samuel (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2021: Anais do XI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2021)
Nanosatellites have become the standard solution for most space systems operating in Low Earth Orbit (LEO). However, this category of satellite imposes strong restrictions on the energy consumption of its subsystems due to the small size of its solar panels. This work presents a parallel software-defined multi-user Phase Shift Keying (PSK) receiver for a nanosatellite payload that will serve the Global Open coLlecting Data System (GOLDS), a message storage and forwarding system. For this, we chose the GAP8, an embedded multi-core RISC-V microprocessor. We use a parallel approach and dynamic voltage and frequency scaling (DVFS) to implement complex signal processing ensuring low power consumption and meeting the real-time operating condition. The receiver’s input signals are 400 bps Machested encoded $± π/ 3 -$ PSK burst signals from terrestrial platforms, and the communication channel was modeled as AWGN with an independent flat fading per PSK signal. A MATLAB reference model was used for functional validation of the proposed implementation. Up to 12 signals can be decoded simultaneously requiring a maximum power consumption of 41 mW. The use of DVFS provided a maximum savings of 43% in dissipated power and 12% in energy consumption.